Porous ceramic skeleton / metal composite wear-resistant part and preparation method thereof
By using 3D printing and high-temperature molten steel casting technology, porous ceramic skeleton/metal composite wear-resistant parts were prepared, which solved the problems of weak interfacial bonding, thermal stress concentration and high cost of ceramic-reinforced metal materials, and achieved high bonding strength and wear resistance, thus improving service life.
Patent Information
- Application Number
- CN202511059775.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-30
- Publication Date
- 2025-11-04
AI Technical Summary
Existing ceramic-reinforced metal wear-resistant materials suffer from problems such as weak interfacial bonding, concentrated thermal stress, insufficient casting penetration depth, and high cost, which affect their widespread application in industries such as cement building materials, power, and mining.
A porous interpenetrating organic mold was prepared using 3D printing technology. Combined with ceramic slurry injection molding and high-temperature steel molten metal casting, Fe-Ni@Cr particles formed an interface bridge, TiC-WC composite powder improved hardness, and ammonium polyacrylate-zwitterionic polymer and composite sodium silicate-nano SiO2 sol improved wettability and bonding strength, forming a porous ceramic skeleton/metal composite wear-resistant part.
It achieves high bonding strength and wear resistance between ceramics and metals, avoids interface cracking, improves service life, and reduces costs.
Smart Images

Figure CN120885666A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of wear-resistant composite materials, and particularly relates to a porous ceramic framework / metal composite wear-resistant part and a preparation method thereof. BACKGROUND
[0002] The ceramic metal composite wear-resistant material is mainly applied to crushing and grinding equipment in the cement building material, electric power, mine and glass fiber industries, and is mainly ceramic particle or powder metallurgy stud enhanced iron-based composite wear-resistant material. Compared with the traditional metal wear-resistant material, the service life is increased, but the development and wide application of the composite wear-resistant material are restricted by the problems such as poor wettability of the ceramic particle and the metal matrix, large difference in the thermal expansion coefficient, low interface bonding strength, high requirement for the casting and infiltration process and high price of the stud.
[0003] The patent application with the publication number CN115806444A discloses a gradient porous ceramic-metal composite connecting part and a preparation method thereof. The ceramic modulus is taken as the upper limit of the design variable, the metal modulus is taken as the lower limit of the design variable, and based on the stress matching in the ceramic-metal composite material connecting process, a three-dimensional model of the gradient porous ceramic structure with the gradually changed ceramic-metal composite structure modulus is designed. However, the metal plating layer thickness reaches 100-500 microns as required in claim 8, but it is difficult to realize uniform immersion in the complex pore channel (especially the gradient structure) of the porous ceramic. The implementation example is achieved through 2-3 times of immersion, and the deep hole penetration limit is not considered, and the actual surface accumulation and internal non-coverage are easily formed.
[0004] The ceramic reinforced metal wear-resistant material in the prior art mainly has the following bottlenecks: ① weak interface bonding: the wetting angle of the ceramic particle and the metal matrix is > 90°, resulting in micro pores in the interface; ② thermal stress concentration: the difference in the thermal expansion coefficient of Al2O3 ceramic and steel leads to interface cracking in the cooling process; ③ insufficient casting and infiltration depth: the metal liquid can only penetrate the ceramic layer with a depth of ≤5 mm under gravity casting, and the thickness of the composite layer is limited; ④ high cost: the ceramic stud cost accounts for more than 60% in the stud type composite part. Therefore, it is urgent to develop a porous ceramic framework / metal composite wear-resistant part to improve the wettability, infiltration effect and bonding strength between the ceramic and the metal. SUMMARY
[0005] The purpose of the present application is to provide a porous ceramic framework / metal composite wear-resistant part and a preparation method thereof to solve the problems of low bonding strength between the ceramic and the metal and poor wear resistance.
[0006] The purpose of the present application can be achieved by the following technical solutions:
[0007] A preparation method of a porous ceramic framework / metal composite wear-resistant part, comprising the following steps:
[0008] S1, a porous interpenetrating organic mold with a thickness of 30-50 mm is prepared by 3D printing technology; the mold is placed in a closed device, vacuumed for 10-15 minutes; ceramic slurry is injected, a pressure of 0.5-1 MPa is applied, pressure is maintained for 30-40 minutes, and the temperature is 80-100℃ for 2-2.5 hours of drying to obtain a green body;
[0009] S2, after cooling and forming, the green body is taken out, heated to 300-600℃ at a rate of 3-5℃ / min, calcined for 2-2.5 hours, and cooled to obtain a porous interpenetrating ceramic skeleton;
[0010] S3, the ceramic skeleton is arranged and fixed in the sand mold according to the design, and a metal liquid channel is reserved; a high-temperature steel solution at 1550-1650℃ is poured, and naturally cooled to below 100℃; after heat treatment and machining, a porous ceramic skeleton / metal composite wear-resistant part is obtained.
[0011] Further, the ceramic slurry comprises ceramic powder, Fe-Ni@Cr, composite sodium silicate-nano SiO2 sol, polyacrylamide-zwitterionic polymer, carboxylated carbon nanotubes and hydroxypropyl methyl cellulose.
[0012] Further, the weight ratio of the ceramic powder, Fe-Ni@Cr, composite sodium silicate-nano SiO2 sol, polyacrylamide-zwitterionic polymer, carboxylated carbon nanotubes and hydroxypropyl methyl cellulose is (6-7):(1-1.5):(2-2.5):(0.3-0.5):(0.1-0.2):(0.05-0.1).
[0013] Further, the ceramic slurry is prepared by the following steps:
[0014] The ceramic powder, Fe-Ni@Cr, composite sodium silicate-nano SiO2 sol, polyacrylamide-zwitterionic polymer, carboxylated carbon nanotubes and hydroxypropyl methyl cellulose are mixed, the pH is adjusted to 8.6-8.9, the temperature is controlled at 23-26℃, and stirring is performed for 30-40 minutes to obtain the ceramic slurry.
[0015] Further, the ceramic powder comprises 75-85 parts of ZTA (ZrO2 toughened Al2O3) and 15-25 parts of TiC-WC composite powder; the mass ratio of TiC and WC in the TiC-WC composite powder is (3-3.5):1.
[0016] Further, the Fe-Ni@Cr is prepared by the following steps:
[0017] (1) dissolving nickel chloride hexahydrate and ferrous chloride in a methanol aqueous solution, adding hydrazine hydrate dropwise, and hydrothermally reacting at 160-170℃ for 6-6.5h to obtain an iron-nickel alloy powder; and immersing the iron-nickel alloy powder in an 8%-12% PdCl2 solution for 5-10 minutes to obtain a pretreated iron-nickel alloy powder;
[0018] (2) mixing CrCl3·6H2O, NaH2PO2·H2O, sodium citrate and NH4Cl, adjusting the pH to 4.5-5 to obtain a chemical chromium plating solution; dispersing the pretreated iron-nickel alloy powder in the plating solution, heating and stirring, reacting in a nitrogen atmosphere, centrifuging and washing, and vacuum drying to obtain Fe-Ni@Cr.
[0019] Further, the weight ratio of the nickel chloride hexahydrate, the methanol aqueous solution and the hydrazine hydrate is (60-70):(10-12):(20-30):(15-25).
[0020] Further, the weight ratio of the CrCl2·6H2O, the NaH2PO2·H2O, the sodium citrate and the NH4Cl is (12-17):(22-27):(25-35):(8-12).
[0021] Further, the weight ratio of the pretreated iron-nickel alloy powder and the plating solution is 1:(45-50).
[0022] Further, the composite sodium silicate-nano SiO2 sol is prepared by the following steps:
[0023] 45-55 parts of a sodium silicate aqueous solution and 15-25 parts of a nano SiO2 sol are ultrasonically dispersed for 30-40 minutes to obtain the composite sodium silicate-nano SiO2 sol.
[0024] Further, the polyammonium acrylate-zwitterionic polymer is prepared by the following steps:
[0025] A PPA (polyammonium acrylate) solution and deionized water are heated and mixed; SBMA (sulfobetaine) is added and dissolved by heating, and the pH is adjusted to 8.7-8.9; the mixture is stirred and heated, silicone antifoam is added, and the polyammonium acrylate-zwitterionic polymer is obtained by filtration.
[0026] Further, the weight ratio of the PPA and the SBMA is (3-3.5):1.
[0027] Further, the 3D printed shape can be one of non-porous, circular, triangular, quadrilateral and hexagonal.
[0028] Further, the porous interpenetrating organic mold is made of a non-toxic organic foam / sponge.
[0029] Further, the mold porosity is designed to be 40% to 60%, and the pore size distribution is 500 to 2000 mu m.
[0030] Further, the drying is 80 to 100 DEG C drying for 2 to 2.5 hours.
[0031] Further, the heat treatment process is to heat to 950 to 1100 DEG C, heat preservation for 6 to 10 hours, air quenching to room temperature, and then tempering at 450 to 580 DEG C, heat preservation for 6 to 8.5 hours, furnace cooling to 60 to 80 DEG C and discharging.
[0032] Further, the steel solution comprises C: 2.2% to 3%, Cr: 20% to 27%, Mn: 1% to 1.5%, Ni: 0.2% to 0.5%, W: 1% to 2%, and Fe: the balance.
[0033] A porous ceramic framework / metal composite wear-resistant part is prepared by the preparation method of the composite wear-resistant part.
[0034] The beneficial effects of the present application are:
[0035] (1) The present application imparts high wear resistance by adopting a ceramic phase, provides high toughness by adopting a metal matrix, and the two complement each other through a "porous interpenetrating structure". In the ceramic framework, ZTA (ZrO2 toughened Al2O3) uses the phase transformation toughening effect of ZrO2 (volume expansion when tetragonal phase to monoclinic phase transition can offset crack propagation stress) to solve the problem of high brittleness of pure Al2O3; in the TiC-WC composite powder, TiC has high hardness and good compatibility with the ceramic phase, and WC has excellent wear resistance, and the combination of the two further improves the overall hardness of the ceramic phase, providing the core wear resistance of the wear-resistant part. The high-temperature steel solution as the metal matrix has high toughness and carrying capacity, can buffer external impact stress, and avoid brittle fracture failure of the ceramic framework. The porous interpenetrating structure forms "mechanical interlocking" between the ceramic framework and the metal matrix, the ceramic bears the wear stress, and the metal disperses the load, and the two achieve "wear resistance without brittle fracture".
[0036] (2) The Fe-Ni@Cr adopted in the present application solves the problem of easy oxidation of traditional alloy powder directly mixed, and uses Ni powder as the core and forms a continuous shell layer by chemical plating of Cr on the surface. It has an interface bridging effect: Ni has excellent compatibility with the steel matrix (Ni-Fe alloying), the addition of Fe reduces the thermal expansion coefficient of the nickel-based core, forms a gradual transition layer between the ceramic (low expansion) and the metal matrix, improves the impact strength, and Cr can form a dense oxide film (Cr2O3) to enhance the oxidation resistance. The Fe-Ni@Cr particles are uniformly dispersed in the ceramic framework, and can react with the high-temperature steel liquid to form a gradient diffusion layer during metal pouring, thereby reducing the interface stress difference between the ceramic (high hardness, low plasticity) and the metal (low hardness, high plasticity), and avoiding interface cracking.
[0037] (3) The ammonium polyacrylate-zwitterionic polymer used in the present application as a dispersant, the zwitterionic group (sulfobetaine) can prevent ceramic particles from agglomeration through the dual action of electrostatic repulsion and steric hindrance; the composite sodium silicate-nano SiO2 sol as a binder, the sodium silicate provides inorganic bonding strength, the nano SiO2 can fill the gap between particles and enhance the flowability of the slurry, and the combination of the two improves the strength of the green body after drying. BRIEF DESCRIPTION OF DRAWINGS
[0038] The present application will be further described below in conjunction with the drawings.
[0039] Figure 1 is a schematic diagram of the 3D printed porous interpenetrating organic mold of the present application;
[0040] Figure 2 is a physical photo of the 3D printed porous interpenetrating organic mold of the present application;
[0041] Figure 3 is a schematic diagram of the process of the ceramic slurry pressure injection molding of the present application. DETAILED DESCRIPTION
[0042] The specific embodiments of the present application will be described in detail below, but it should be understood that the protection scope of the present application is not limited by the specific embodiments.
[0043] Example 1
[0044] This embodiment provides a porous ceramic framework / metal composite wear-resistant part, which is prepared by the following steps:
[0045] S1, dissolve 65 parts of nickel chloride hexahydrate and 11 parts of ferrous chloride in 35 parts of methanol aqueous solution, add 20 parts of hydrazine hydrate dropwise, and hydrothermal reaction at 170℃ for 6h to obtain iron-nickel alloy powder; immerse the iron-nickel alloy powder in a 10% PdCl2 solution for 5 minutes to obtain pretreated iron-nickel alloy powder; mix 15 parts of CrCl3·6H2O, 25 parts of NaH2PO2·H2O, 30 parts of sodium citrate and 10 parts of NH4Cl, and adjust the pH to 4.5 to obtain a chemical chromium plating solution; disperse the pretreated iron-nickel alloy powder in the plating solution (solid-liquid weight ratio 1:50), mechanically stir (200rpm), react at 90℃ in nitrogen atmosphere for 30 minutes, centrifugal separation, ethanol washing 3 times, vacuum drying at 60℃ to obtain Fe-Ni@Cr;
[0046] S2, 50 parts of sodium silicate aqueous solution and 20 parts of nano-SiO2 sol were ultrasonically dispersed for 30 minutes to prepare a composite sodium silicate-nano-SiO2 sol; 50 parts of deionized water was heated to 40°C, 30 parts of PPA solution was added, and stirred for 10 minutes (300 rpm); 10 parts of SBMA powder was added, and the temperature was increased to 60°C to accelerate dissolution; 5% ammonia water was added dropwise to adjust the pH to 8.8; 50°C was kept for 1h, 0.05% silicone defoamer was added, and sieved through a 400 mesh screen to obtain polyammonium acrylate-zwitterionic polymer;
[0047] S3, 6 parts of ceramic powder (including 80 parts of ZTA and 20 parts of TiC-WC composite powder; the mass ratio of TiC to WC in the TiC-WC composite powder is 3:1), 1.25 parts of Fe-Ni@Cr, 2 parts of composite sodium silicate-nano-SiO2 sol, 0.4 parts of polyammonium acrylate-zwitterionic polymer, 0.1 parts of carboxylated carbon nanotubes, and 0.08 parts of hydroxypropyl methyl cellulose were mixed, the pH was adjusted to 8.8, the temperature was controlled at 25°C, and stirred for 30 minutes to obtain a ceramic slurry;
[0048] S4, a circular porous interpenetrating organic 40mm thick porous interpenetrating organic mold was prepared by using 3D printing technology (as shown in Figures 1-2 ), the porosity of the mold was designed to be 50%, and the pore size distribution was 1000μm. The mold was placed horizontally in a sealed device. First, the inside of the box was evacuated to maintain a vacuum for 15 minutes, then the ceramic slurry (as shown in Figure 3 ) was injected into the box, a pressure of 0.5MPa was applied, and the pressure was maintained for 30 minutes. The mold was dried at 90°C for 2h to obtain a green body. After waiting for cooling and forming, the sealed box was opened and the green body was taken out and placed in a muffle furnace. The temperature was increased to 550°C at a rate of 5°C / min, and calcined for 2h. After the porous interpenetrating organic mold was fully burned and decomposed, it was naturally cooled to room temperature, thereby obtaining a porous interpenetrating ceramic framework;
[0049] S5, the prepared ceramic framework was placed in a sand mold, and arranged and fixed in order according to the design requirements of the wear-resistant part. The sand box was closed, and a 1600°C high-temperature steel solution (the steel solution includes C: 2.2%~3%, Cr: 20%~27%, Mn: 1%~1.5%, Ni: 0.2%~0.5%, W: 1%~2%, Fe: balance) was poured. Natural temperature was maintained until the temperature cooled to below 100°C. The sand box was opened, and a ceramic framework metal composite wear-resistant casting was obtained. After cleaning, polishing, heat treatment (heating to 1000°C, maintaining for 8h, air quenching to room temperature, tempering at 500°C for 7h, furnace cooling to 80°C and then taking out), and machining, a porous ceramic framework / metal composite wear-resistant part was obtained.
[0050] Example 2
[0051] The embodiment is different from example 1 in that the preparation conditions of S4-S5 are adjusted, and the specific implementation of S4-S5 is as follows:
[0052] S4, a circular porous interpenetrating organic 40mm thick porous interpenetrating organic mold (as shown in Figures 1-2 ) is made by using 3D printing technology, the porosity of the mold is designed to be 40%, and the pore size distribution is 1500μm. The mold is placed flat in a sealed device. First, the box is evacuated to maintain a vacuum for 10 minutes, then ceramic slurry (as shown in Figure 3 ) is injected into the box, 1MPa pressure is applied, and pressure is maintained for 40 minutes. The slurry is dried at 90℃ for 2h to obtain a green body. After waiting for cooling and forming, the sealed box is opened and the green body is taken out and placed in a muffle furnace. The temperature is raised to 350℃ at a rate of 3℃ / min, and the temperature is maintained for 2.5 hours. After the porous interpenetrating organic mold is fully burned and decomposed, it is naturally cooled to room temperature, thereby obtaining a porous interpenetrating ceramic framework.
[0053] S5, the prepared ceramic framework is placed in a sand mold, and is arranged and fixed in sequence according to the design requirements of the wear-resistant part. The sand box is closed, and a 1570℃ high-temperature steel solution (the steel solution includes C: 2.2%~3%, Cr: 20%~27%, Mn: 1%~1.5%, Ni: 0.2%~0.5%, W: 1%~2%, Fe: balance) is poured. Natural temperature maintenance is performed until the temperature cools to below 100℃. The sand box is opened, and the porous ceramic framework / metal composite wear-resistant part is obtained after cleaning, polishing, heat treatment (heating to 1050℃, maintaining for 9 hours, air quenching to room temperature, tempering at 550℃, maintaining for 6 hours, and furnace cooling to 60℃ before discharging), and machining.
[0054] The remaining raw materials and preparation process are the same as in example 1.
[0055] Example 3
[0056] The embodiment is different from example 1 in that the preparation conditions of S4-S5 are adjusted, and the specific implementation of S4-S5 is as follows:
[0057] S4, a circular porous interpenetrating organic 40mm thick porous interpenetrating organic mold (as shown in Figures 1-2 ) is made by using 3D printing technology, the porosity of the mold is designed to be 40%, and the pore size distribution is 1500μm. The mold is placed flat in a sealed device. First, the box is evacuated to maintain a vacuum for 10 minutes, then ceramic slurry (as shown in Figure 3 ) is injected into the box, 1MPa pressure is applied, and pressure is maintained for 40 minutes. The slurry is dried at 90℃ for 2h to obtain a green body. After waiting for cooling and forming, the sealed box is opened and the green body is taken out and placed in a muffle furnace. The temperature is raised to 350℃ at a rate of 3℃ / min, and the temperature is maintained for 2.5 hours. After the porous interpenetrating organic mold is fully burned and decomposed, it is naturally cooled to room temperature, thereby obtaining a porous interpenetrating ceramic framework.
[0058] S5, placing the prepared ceramic framework into a sand mold, arranging and fixing according to the design requirements of the wear-resistant part in sequence, closing the sand box, pouring a high-temperature steel solution (the steel solution includes C: 2.2%~3%, Cr: 20%~27%, Mn: 1%~1.5%, Ni: 0.2%~0.5%, W: 1%~2%, Fe: balance) at 1650℃, naturally heat preservation until cooled to below 100℃, opening the sand box, cleaning and polishing, heat treatment (heating to 980℃, heat preservation for 10 hours, air quenching to room temperature, tempering at 500℃, heat preservation for 6 hours, furnace cooling to 70℃ and discharging), machining, to obtain the porous ceramic framework / metal composite wear-resistant part.
[0059] The remaining raw materials and preparation process are the same as those of Example 1.
[0060] Example 4
[0061] Compared with Example 1, the difference of the present embodiment is that the amount of Fe-Ni@Cr is increased, and the specific implementation of S3 is as follows:
[0062] S3, mixing 6.5 parts of ceramic powder (including 80 parts of ZTA and 20 parts of TiC-WC composite powder; the mass ratio of TiC to WC in the TiC-WC composite powder is 3:1), 1.5 parts of Fe-Ni@Cr, 2.25 parts of composite sodium silicate-nano SiO2 sol, 0.3 parts of polyammonium acrylate-zwitterionic polymer, 0.1 parts of carboxylated carbon nanotube and 0.05 parts of hydroxypropyl methyl cellulose, adjusting the pH to 8.7, controlling the temperature at 24℃, and stirring for 30 minutes to obtain a ceramic slurry;
[0063] The remaining raw materials and preparation process are the same as those of Example 1.
[0064] Example 5
[0065] Compared with Example 1, the difference of the present embodiment is that the amount of Fe-Ni@Cr is reduced, and the specific implementation of S3 is as follows:
[0066] S3, mixing 7 parts of ceramic powder (including 85 parts of ZTA and 15 parts of TiC-WC composite powder; the mass ratio of TiC to WC in the TiC-WC composite powder is 3.5:1), 1 part of Fe-Ni@Cr, 2.5 parts of composite sodium silicate-nano SiO2 sol, 0.5 parts of polyammonium acrylate-zwitterionic polymer, 0.2 parts of carboxylated carbon nanotube and 0.1 parts of hydroxypropyl methyl cellulose, adjusting the pH to 8.9, controlling the temperature at 26℃, and stirring for 40 minutes to obtain a ceramic slurry;
[0067] The remaining raw materials and preparation process are the same as those of Example 1.
[0068] The above steps are as follows Figure 1shown.
[0069] Example 6
[0070] The difference between this embodiment and Example 1 is that the amount of S1-S2 components is adjusted, and the specific implementation of S1-S2 is as follows:
[0071] S1, dissolve 65 parts of nickel chloride hexahydrate and 10 parts of ferrous chloride in 35 parts of methanol aqueous solution, add 20 parts of hydrazine hydrate dropwise, and hydrothermal reaction at 170°C for 6h to obtain iron-nickel alloy powder; immerse the iron-nickel alloy powder in a 10% PdCl2 solution for 5 minutes to obtain pretreated iron-nickel alloy powder; mix 12 parts of CrCl3·6H2O, 27 parts of NaH2PO2·H2O, 25 parts of sodium citrate and 12 parts of NH4Cl, and adjust the pH to 4.5 to obtain a chemical chromium plating solution; disperse the pretreated iron-nickel alloy powder in the plating solution (solid-liquid weight ratio 1:50), mechanically stir (200 rpm), and react at 90°C in a nitrogen atmosphere for 30 minutes; centrifugal separation, ethanol washing 3 times, 60°C vacuum drying, to obtain Fe-Ni@Cr;
[0072] S2, prepare a composite sodium silicate-nano SiO2 sol by ultrasonic dispersion of 45 parts of sodium silicate aqueous solution and 25 parts of nano SiO2 sol for 30 minutes; heat 50 parts of deionized water to 40°C, add 30 parts of PPA solution, and stir for 10 minutes (300 rpm); add 10 parts of SBMA powder, and accelerate dissolution by heating to 60°C; add 5% ammonia water dropwise, and adjust the pH to 8.8; 50°C, stirring for 1h, adding 0.05% silicone defoamer, passing through a 400 mesh screen, to obtain polyammonium polyacrylate-zwitterionic polymer;
[0073] The remaining raw materials and preparation process remain the same as in Example 1.
[0074] Example 7
[0075] The difference between this embodiment and Example 1 is that the amount of S1-S2 components is adjusted, and the specific implementation of S1-S2 is as follows:
[0076] S1, dissolve 65 parts of nickel chloride hexahydrate and 10 parts of ferrous chloride in 35 parts of methanol aqueous solution, add 20 parts of hydrazine hydrate dropwise, and hydrothermal reaction at 170°C for 6h to obtain iron-nickel alloy powder; immerse the iron-nickel alloy powder in a 10% PdCl2 solution for 5 minutes to obtain pretreated iron-nickel alloy powder; mix 12 parts of CrCl3·6H2O, 27 parts of NaH2PO2·H2O, 25 parts of sodium citrate and 12 parts of NH4Cl, and adjust the pH to 4.5 to obtain a chemical chromium plating solution; disperse the pretreated iron-nickel alloy powder in the plating solution (solid-liquid weight ratio 1:50), mechanically stir (200 rpm), and react at 90°C in a nitrogen atmosphere for 30 minutes; centrifugal separation, ethanol washing 3 times, 60°C vacuum drying, to obtain Fe-Ni@Cr;
[0077] S2, 55 parts of sodium silicate aqueous solution and 15 parts of nano-SiO2 sol were ultrasonically dispersed for 30 minutes to prepare a composite sodium silicate-nano-SiO2 sol; 50 parts of deionized water was heated to 40°C, 30 parts of PPA solution was added, and stirred for 10 minutes (300 rpm); 10 parts of SBMA powder was added, and the temperature was increased to 60°C for accelerated dissolution; 5% ammonia water was added dropwise, and the pH was adjusted to 8.8; 50°C was kept for 1 hour of stirring, 0.05% silicone defoaming agent was added, and a 400-mesh screen was used to obtain a polyammonium polyacrylate-zwitterionic polymer;
[0078] The remaining raw materials and preparation process were the same as in Example 1.
[0079] Comparative Example 1
[0080] This comparative example is different from Example 1 in that Fe-Ni@Cr is replaced by a simple mixture of a Ni source, a Fe source, and a Cr source, and the specific implementation steps of S1-S3 are as follows:
[0081] S1, 65 parts of nickel chloride hexahydrate and 11 parts of ferrous chloride and 15 parts of CrCl3·6H2O were mechanically stirred (200 rpm) at 90°C in a nitrogen atmosphere for 30 minutes, centrifuged, washed with ethanol for 3 times, and vacuum dried at 60°C to obtain a Fe / Ni / Cr mixture;
[0082] S2, 50 parts of sodium silicate aqueous solution and 20 parts of nano-SiO2 sol were ultrasonically dispersed for 30 minutes to prepare a composite sodium silicate-nano-SiO2 sol; 50 parts of deionized water was heated to 40°C, 30 parts of PPA solution was added, and stirred for 10 minutes (300 rpm); 10 parts of SBMA powder was added, and the temperature was increased to 60°C for accelerated dissolution; 5% ammonia water was added dropwise, and the pH was adjusted to 8.8; 50°C was kept for 1 hour of stirring, 0.05% silicone defoaming agent was added, and a 400-mesh screen was used to obtain a polyammonium polyacrylate-zwitterionic polymer;
[0083] S3, 6 parts of ceramic powder (including 80 parts of ZTA and 20 parts of TiC-WC composite powder; the mass ratio of TiC to WC in the TiC-WC composite powder is 3:1), 1.25 parts of the Ni / Cr mixture, 2 parts of the composite sodium silicate-nano-SiO2 sol, 0.4 parts of the polyammonium polyacrylate-zwitterionic polymer, 0.1 parts of carboxylated carbon nanotubes, and 0.08 parts of hydroxypropyl methyl cellulose were mixed, the pH was adjusted to 8.8, the temperature was controlled at 25°C, and stirring was performed for 30 minutes to obtain a ceramic slurry;
[0084] The remaining raw materials and preparation process were the same as in Example 1.
[0085] Comparative Example 2
[0086] The comparative example is compared with example 1, the difference is that no Fe source is added, and the specific implementation steps of S1 are as follows:
[0087] S1, 65 parts of nickel chloride hexahydrate are dissolved in 35 parts of methanol aqueous solution, 20 parts of hydrazine hydrate is added dropwise, and hydrothermal reaction is carried out at 170 DEG C for 6h to obtain iron-nickel alloy powder; the iron-nickel alloy powder is immersed in a 10% PdCl2 solution for 5 minutes to obtain pretreated iron-nickel alloy powder; 17 parts of CrCl3·6H2O, 22 parts of NaH2PO2·H2O, 35 parts of sodium citrate and 8 parts of NH4Cl are uniformly mixed, and the pH is adjusted to 5 to obtain a chemical chromium plating solution; the pretreated iron-nickel alloy powder is dispersed in the plating solution (solid-liquid weight ratio 1:50), mechanically stirred (200 rpm), and reacted at 90 DEG C in a nitrogen atmosphere for 30 minutes; centrifugal separation, ethanol washing 3 times, and vacuum drying at 60 DEG C to obtain Ni@Cr;
[0088] The remaining raw materials and preparation process remain the same as in example 1.
[0089] Comparative example 3
[0090] The comparative example is compared with example 1, the difference is that no nano-SiO2 sol is added, and the specific implementation steps of S1-S3 are as follows:
[0091] S1, 65 parts of nickel chloride hexahydrate and 11 parts of ferrous chloride are dissolved in 35 parts of methanol aqueous solution, 20 parts of hydrazine hydrate is added dropwise, and hydrothermal reaction is carried out at 170 DEG C for 6h to obtain iron-nickel alloy powder; the iron-nickel alloy powder is immersed in a 10% PdCl2 solution for 5 minutes to obtain pretreated iron-nickel alloy powder; 17 parts of CrCl3·6H2O, 22 parts of NaH2PO2·H2O, 35 parts of sodium citrate and 8 parts of NH4Cl are uniformly mixed, and the pH is adjusted to 5 to obtain a chemical chromium plating solution; the pretreated iron-nickel alloy powder is dispersed in the plating solution (solid-liquid weight ratio 1:50), mechanically stirred (200 rpm), and reacted at 90 DEG C in a nitrogen atmosphere for 30 minutes; centrifugal separation, ethanol washing 3 times, and vacuum drying at 60 DEG C to obtain Fe-Ni@Cr;
[0092] S2, 50 parts of deionized water is heated to 40 DEG C, 30 parts of PPA solution is added, and stirred for 10 minutes (300 rpm); 10 parts of SBMA powder is added, and the temperature is increased to 60 DEG C to accelerate dissolution; 5% ammonia water is added dropwise, and the pH is adjusted to 8.8; 50 DEG C is kept for 1h, 0.05% silicone defoaming agent is added, and the mixture is passed through a 400 mesh screen to obtain polyammonium polyacrylate-zwitterionic polymer;
[0093] S3, 6 parts of ceramic powder (including 80 parts of ZTA and 20 parts of TiC-WC composite powder; the mass ratio of TiC and WC in the TiC-WC composite powder is 3:1), 1.25 parts of Fe-Ni@Cr, 2 parts of sodium silicate, 0.4 parts of polyammonium acrylate-zwitterionic polymer, 0.1 part of carboxylated carbon nanotubes and 0.08 part of hydroxypropyl methyl cellulose are mixed, the pH is adjusted to 8.8, the temperature is controlled at 25°C, and stirring is performed for 30 minutes to obtain a ceramic slurry;
[0094] The remaining raw materials and preparation process remain the same as in Example 1.
[0095] Comparative Example 4
[0096] This comparative example is compared with Example 1, the difference is that SBMA is not added, and the specific implementation steps of S1-S3 are as follows:
[0097] S1, 65 parts of nickel chloride hexahydrate and 11 parts of ferrous chloride are dissolved in 35 parts of methanol aqueous solution, 20 parts of hydrazine hydrate is added dropwise, and hydrothermal reaction is performed at 170°C for 6h to obtain iron-nickel alloy powder; the iron-nickel alloy powder is immersed in a 10% PdCl2 solution for 5 minutes to obtain pretreated iron-nickel alloy powder; 15 parts of CrCl3·6H2O, 25 parts of NaH2PO2·H2O, 30 parts of sodium citrate and 10 parts of NH4Cl are mixed to obtain a chemical chromium plating solution with a pH of 4.5; the pretreated iron-nickel alloy powder is dispersed in the plating solution (solid-liquid weight ratio 1:50), mechanically stirred (200 rpm), and reacted at 90°C in a nitrogen atmosphere for 30 minutes; centrifugal separation, ethanol washing 3 times, and vacuum drying at 60°C to obtain Fe-Ni@Cr;
[0098] S2, 50 parts of sodium silicate aqueous solution and 20 parts of nano-SiO2 sol are ultrasonically dispersed for 30 minutes to obtain a composite sodium silicate-nano-SiO2 sol;
[0099] S3, 6 parts of ceramic powder (including 80 parts of ZTA and 20 parts of TiC-WC composite powder; the mass ratio of TiC and WC in the TiC-WC composite powder is 3:1), 1.25 parts of Fe-Ni@Cr, 2 parts of composite sodium silicate-nano-SiO2 sol, 0.4 parts of polyammonium acrylate, 0.1 part of carboxylated carbon nanotubes and 0.08 part of hydroxypropyl methyl cellulose are mixed, the pH is adjusted to 8.8, the temperature is controlled at 25°C, and stirring is performed for 30 minutes to obtain a ceramic slurry;
[0100] The remaining raw materials and preparation process remain the same as in Example 1.
[0101] Comparative Example 5
[0102] This comparative example is compared with Example 1, the difference is that polyammonium acrylate-zwitterionic polymer is not added, and the specific implementation steps of S1-S3 are as follows:
[0103] S1, dissolve 65 parts of nickel chloride hexahydrate and 11 parts of ferrous chloride in 35 parts of methanol aqueous solution, add 20 parts of hydrazine hydrate dropwise, hydrothermal reaction at 170℃ for 6h to obtain iron-nickel alloy powder; immerse the iron-nickel alloy powder in a 10% PdCl2 solution for 5 minutes to obtain pretreated iron-nickel alloy powder; mix 15 parts of CrCl3·6H2O, 25 parts of NaH2PO2·H2O, 30 parts of sodium citrate and 10 parts of NH4Cl, adjust the pH to 4.5 to obtain a chemical chromium plating solution; disperse the pretreated iron-nickel alloy powder in the plating solution (solid-liquid weight ratio 1:50), mechanically stir (200 rpm), react at 90℃ in a nitrogen atmosphere for 30 minutes, centrifugal separation, ethanol washing 3 times, vacuum drying at 60℃ to obtain Fe-Ni@Cr;
[0104] S2, prepare a composite sodium silicate-nano SiO2 sol by ultrasonic dispersion of 50 parts of sodium silicate aqueous solution and 20 parts of nano SiO2 sol for 30 minutes;
[0105] S3, mix 6 parts of ceramic powder (including 80 parts of ZTA and 20 parts of TiC-WC composite powder; the mass ratio of TiC to WC in the TiC-WC composite powder is 3:1), 1.25 parts of Fe-Ni@Cr, 2 parts of composite sodium silicate-nano SiO2 sol, 0.1 parts of carboxylated carbon nanotubes and 0.08 parts of hydroxypropyl methyl cellulose, adjust the pH to 8.8, control the temperature at 25℃, stir for 30 minutes to obtain a ceramic slurry;
[0106] The remaining raw materials and preparation process are the same as those of Example 1.
[0107] Performance test
[0108] Interface bonding strength (MPa): according to ASTM D1002-10 (2019) "Standard Test Method for Apparent Shear Strength of Single-Lap-Jointed Adhesive-Bonded Metal Specimens by Tension Load", the interface bonding strength of the composite wear-resistant parts prepared in the examples and comparative examples was tested;
[0109] Wear resistance (ε = volume wear loss, mm 3 ): according to GB / T 12444-2006 "Metallic Materials - Wear Testing - 1 : Standard Test Method for Dry Sliding Wear; and 2: Load Controlled Sliding Block-on-Ring Wear Test", the wear resistance of the composite wear-resistant parts prepared in the examples and comparative examples was tested;
[0110] Compressive strength (MPa): according to GB / T 7314-2017 "Metallic Materials - Room Temperature Compression Test Method", the compressive strength of the composite wear-resistant parts prepared in the examples and comparative examples was tested;
[0111] Impact toughness (J / cm 2) Impact toughness test was carried out on the composite wear-resistant parts prepared in the examples and comparative examples according to GB / T 229-2020 "Metallic materials Charpy pendulum impact test method";
[0112] The results are shown in Table 1:
[0113] Table 1
[0114]
[0115] As can be seen from Table 1, the performance of Examples 1-3 remains stable by adjusting process parameters such as mold porosity and pouring temperature, showing the reliability of the process; by adjusting the amount of Fe-Ni@Cr in Examples 4-5, it is found that within the range of 1-1.5 parts, the wear resistance and toughness can be balanced, and excessive or insufficient amount will cause the compressive strength to decrease slightly. This is consistent with the design concept of "porous interpenetrating structure" to realize the synergy of ceramic wear resistance and metal toughness - the combination of high compressive strength (1088-1240 MPa) and high impact toughness (15.6-17.9 J / cm 2 ) in the examples is a direct manifestation of the ceramic skeleton bearing wear stress and the metal matrix dispersing impact load.
[0116] The core-shell structure of Fe-Ni@Cr is the key to improving the interface performance: after replacing the core-shell structure of Fe-Ni@Cr with a simple mixture of Ni, Fe and Cr in Comparative Example 1, the interfacial bonding strength decreases by 42.1% (from 152 MPa to 88 MPa), and the volume wear increases by 94.3% (from 3.5 mm 3 to 6.8 mm 3 ), indicating that the core-shell structure effectively reduces the interface stress difference between ceramic and metal through the synergistic effect of "Ni-Fe alloying compatible with metal matrix, Cr shell layer anti-oxidation, and Fe adjusting the thermal expansion coefficient"; in Comparative Example 2, the performance is further deteriorated (wear amount 7.2 mm 3 , impact toughness 13.4 J / cm 2 ) due to the lack of Fe source, which confirms the key role of Fe in building a gradual transition layer. In Comparative Example 3, the green body density decreases due to the lack of nano-SiO2, resulting in significantly lower wear resistance (7.2 mm 3 ) and compressive strength (900 MPa) than Example 1, which demonstrates the advantages of nano-SiO2 filling the gap between particles and enhancing the flowability of the slurry. In addition, the dispersing effect of polyacrylic acid ammonium-zwitterionic polymer (PPA-SBMA) is indispensable, and the volume wear amounts of Comparative Example 4 (without SBMA) and Comparative Example 5 (without the polymer) are 7.7 mm 3 and 8.0 mm 3 , respectively, which are much higher than the 3.5 mm 3The results show that the ceramic particles are prevented from agglomerating by electrostatic repulsion and steric hindrance in Example 1, and the uniform distribution of the ceramic phase is ensured.
[0117] The above disclosure is only several specific embodiments of the present application, but the embodiments of the present application are not limited thereto, and any changes that can be thought of by those skilled in the art shall fall within the protection scope of the present application.
Claims
1. A method for producing a porous ceramic skeleton / metal composite wear part, characterized by, The method comprises the following steps: S1, using 3D printing to make a 30-50mm thick porous interpenetrating organic mold, after vacuumizing, injecting ceramic slurry, pressurizing and preserving, drying to get a blank; S2, heating the blank to 300-600℃ at a rate of 3-5℃ / min and calcining to get a porous interpenetrating ceramic framework; S3, fixing the ceramic framework on a sand mold, pouring a 1550-1650℃ steel solution, after cooling, heat treatment and machining to get a porous ceramic framework / metal composite wear-resistant part; The ceramic slurry comprises ceramic powder, Fe-Ni@Cr, composite sodium silicate-nano SiO2 sol, polyammonium acrylate-zwitterionic polymer, carboxylated carbon nanotube and hydroxypropyl methyl cellulose.
2. The method for preparing a porous ceramic skeleton / metal composite wear-resistant part according to claim 1, characterized in that, The ceramic slurry is prepared by the following steps: Mixing ceramic powder, Fe-Ni@Cr, composite sodium silicate-nano SiO2 sol, polyammonium acrylate-zwitterionic polymer, carboxylated carbon nanotube and hydroxypropyl methyl cellulose, adjusting pH to 8.6-8.9, controlling temperature at 23-26℃, stirring for 30-40 minutes to get the ceramic slurry.
3. The method for preparing a porous ceramic skeleton / metal composite wear-resistant part according to claim 2, characterized in that, The weight ratio of the ceramic powder, Fe-Ni@Cr, composite sodium silicate-nano SiO2 sol, polyammonium acrylate-zwitterionic polymer, carboxylated carbon nanotube and hydroxypropyl methyl cellulose is (6-7):(1-1.5):(2-2.5):(0.3-0.5):(0.1-0.2):(0.05-0.1). The ceramic powder comprises 75-85 parts of ZTA (ZrO2 toughened Al2O3) and 15-25 parts of TiC-WC composite powder; the mass ratio of TiC and WC in the TiC-WC composite powder is (3-3.5):
1.
4. The method for preparing a porous ceramic skeleton / metal composite wear-resistant part according to claim 1, characterized in that, The Fe-Ni@Cr is prepared by the following steps: (1) dissolving nickel chloride hexahydrate and ferrous chloride in methanol aqueous solution, adding hydrazine hydrate dropwise under inert atmosphere protection, hydrothermal reaction at 160-170℃ for 6-6.5h to get iron-nickel alloy powder; immersing the iron-nickel alloy powder in 8%-12% PdCl2 solution for 5-10 minutes to get pretreated iron-nickel alloy powder; (2) mixing CrCl3·6H2O, NaH2PO2·H2O, sodium citrate and NH4Cl, adjusting pH to 4.5-5 to get a chemical chromium plating solution; dispersing the pretreated iron-nickel alloy powder in the plating solution, heating and stirring, reacting in nitrogen atmosphere, centrifugal washing, vacuum drying to get Fe-Ni@Cr.
5. The method for preparing a porous ceramic skeleton / metal composite wear-resistant part according to claim 4, characterized in that, The weight ratio of nickel chloride hexahydrate, ferrous chloride, methanol aqueous solution and hydrazine hydrate is (60-70):(10-12):(20-30):(15-25); the weight ratio of CrCl3·6H2O, NaH2PO2·H2O, sodium citrate and NH4Cl is (12-17):(22-27):(25-35):(8-12); the weight ratio of the pretreated iron-nickel alloy powder and the plating solution is 1:(45-50).
6. The method for preparing a porous ceramic skeleton / metal composite wear-resistant part according to claim 1, characterized in that, The composite sodium silicate-nano SiO2 sol is prepared by the following steps: Ultrasonic dispersion of 45-55 parts of sodium silicate aqueous solution and 15-25 parts of nano SiO2 sol for 30-40 minutes to get the sol.
7. The method for preparing a porous ceramic skeleton / metal composite wear-resistant part according to claim 1, characterized in that, The ammonium polyacrylate-zwitterionic polymer is prepared by the following steps: PPA solution and deionized water were heated and mixed; SBMA was added and heated to dissolve, and the pH was adjusted to 8.7-8.9; the mixture was kept warm and stirred, an organosilicon defoamer was added, and the mixture was filtered to obtain ammonium polyacrylate-zwitterionic polymer; the weight ratio of PPA to SBMA was (3-3.5):
1.
8. The method for preparing a porous ceramic skeleton / metal composite wear-resistant part according to claim 1, characterized in that, The 3D printed shape is one of the following: non-porous, circular, triangular, quadrilateral, and hexagonal; the porous interpenetrating organic mold is made of non-toxic organic foam / sponge; the mold porosity is designed to be 40% to 60%, and the pore size distribution is 500 to 2000 μm.
9. The method for preparing a porous ceramic skeleton / metal composite wear-resistant part according to claim 1, characterized in that, The drying process involves drying at 80–100°C for 2–2.5 hours; the heat treatment process involves heating to 950–1100°C, holding at that temperature for 6–10 hours, air quenching to room temperature, then tempering at 450–580°C for 6–8.5 hours, and finally cooling in the furnace to 60–80°C before being removed from the furnace; the molten steel comprises C: 2.2%–3%, Cr: 20%–27%, Mn: 1%–1.5%, Ni: 0.2%–0.5%, W: 1%–2%, and Fe: balance.
10. A porous ceramic matrix / metal composite wear part, characterized in that, It is prepared by the method for preparing composite wear-resistant parts according to any one of claims 1-9.
Citation Information
Patent Citations
Gradient porous ceramic-metal composite connecting piece and preparation method thereof
CN115806444A